Cloud Based Accounting Information Systems for Affiliated Companies - Asmuni, Idris (Prosiding International conference on Information Technology and Business (ICITB), 2023)
For affiliated companies, there is a need to organize an online-based bookkeeping system in order to facilitate the coordination of incoming and outgoing transactions in integrated financial reports. The use of a cloud-based accounting information system will unify separate records to become more reliable and trustworthy in accordance with the regulations in the International Financial Report Standard (IFRS). This paper discusses the implementation of a cloud-based information system and accounting application features in reports produced based on IFRS-guided principles which have a good impact on companies between head office and branchesÂ  in presenting financial reports on time in decision making. However, there are costs that must be a major concern for managers in implementing cloud accounting and must be included as economic expenditure to achieve company goals.Future threats in cloud implementation that users should consider before choosing cloud-based accounting are security issues of company confidential financial dataKeywordsâ€”cloud based , accounting information systems, Affiliated Companies